Addressing trauma in schools: Multitiered service delivery options for practitioners. Issue 3 (25th January 2018) - Reinbergs, Erik J.; Fefer, Sarah A.
Abstract: Hundreds of thousands of children are confronted with traumatic experiences each year in the United States. As trauma‐informed care begins to take hold in schools, school mental health providers (e.g., school psychologists, counselors, and social workers) desire concrete service‐delivery options for students affected by trauma. This article provides examples from the literature via a narrative review of assessment, intervention, and practitioner support options related to childhood trauma. Specific attention is paid to framing concrete school‐based trauma service‐delivery options within a multitiered systems of support model to align with existing school practices. Given the large amount of literature on this topic, this article aims to reduce the barriers practitioners face when looking to implement trauma services in their schools by organizing example practices from the literature in a commonly used service‐delivery framework.